Automorphism groups and Picard groups of additive full subcategories - Hiramatsu, Naoya; Yoshino, Yuji (MATHEMATICA SCANDINAVICA, 2010)
We study category equivalences between additive full subcategories of module categories over commutative rings. And we are able to define the Picard group of additive full subcategories. The aim of this paper is to study the properties of the Picard groups and show that the automorphism group of an additive full subcategory is a semi-direct product of the Picard group with the group of algebra automorphisms of the ring.